2010
DOI: 10.1159/000316696
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Secondary Cataract Prevention: Experimental ex vivo and in vivo Results with Disulfiram, Methotrexate and Actinomycin D

Abstract: Background/Aims: A clinical approach to prevent secondary cataract after lens implantation involves the intraocular application of pharmacological agents. The goals of our study were to develop an ex vivo model to test the drug effectiveness for lens epithelial cell ablation from the basal membrane and to verify the data in rabbit intraocular lens implantation experiments. Methods: Human capsular rhexis specimens were incubated with drugs and the residual cells were differentiated by use of the Live-Dead assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…For the presented application HA was chosen, since HA is commonly used in addition to cellulose derivatives as a viscoelastic biomaterial for routine cataract surgery, serving to stabilize the anterior chamber. Furthermore, the potential of HA loaded with antiproliferative model drugs was studied regarding the effectiveness of local drug delivery for lens epithelial cell ablation from the basal membrane and for prevention of secondary cataract formation [39]. However, in that study pure, non-crosslinked hydrogel was used, as only 2-5 minutes of drug release were needed.…”
Section: Figure 10mentioning
confidence: 99%
“…For the presented application HA was chosen, since HA is commonly used in addition to cellulose derivatives as a viscoelastic biomaterial for routine cataract surgery, serving to stabilize the anterior chamber. Furthermore, the potential of HA loaded with antiproliferative model drugs was studied regarding the effectiveness of local drug delivery for lens epithelial cell ablation from the basal membrane and for prevention of secondary cataract formation [39]. However, in that study pure, non-crosslinked hydrogel was used, as only 2-5 minutes of drug release were needed.…”
Section: Figure 10mentioning
confidence: 99%
“…The results from the current study also indicate that use of methotrexate was associated with a lower incidence of cataract independent of radiotherapy. Treating lens epithelial cells with methotrexate and actinomycin D proved to be an effective method for preventing posterior capsule opacification in rabbits (36). In a retrospective cohort study of children with juvenile idiopathic arthritis-associated uveitis, it was also reported that there was a significantly lower risk of cataract surgery over time in patients treated with methotrexate (37).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous experimental results, 13 an OVD mixture containing actinomycin D plus DL-methotrexate embedded in sodium hyaluronate was chosen to prevent secondary cataract formation. In rabbits, DL-methotrexate (mean molecular weight 454.4 g/mol) and actinomycin D (mean molecular weight 1,255.4 g/mol) were obtained from Sigma-Aldrich Chemie GmbH.…”
Section: Secondary Cataract Preventionmentioning
confidence: 99%